Tissue Distribution Study of Naringin in Rats by Liquid Chromatography-Tandem Mass Spectrometry - Zou, W.; Yang, C.; Liu, M.; Su, W. (Arzneimittelforschung, 2012)
Naringin (CAS 10236-47-2), a flavanone glucoside widely present in fruits of citrus plants, has received extensive studies on its potential effects on health benefits and was recently demonstrated to be a putative antitussive. In this study, we determined the tissue distributions of naringin and its metabolites (naringenin and naringenin’s conjugates) in rats to examine whether they undergo selective uptake by specific organs. Naringin was administered orally to rats at the dose of 42 mg/kg and the concentrations of naringin and its metabolites in tissue compartments were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The areas under curve values in the individual tissues decreased as follows: stomach, small intestine, liver, trachea, muscle, kidney, lung, fat, heart, spleen, ovary, testis, brain for naringin; and liver, stomach, small intestine, kidney, trachea, lung, testis, heart, ovary, fat, spleen, muscle, brain for total naringenin (including free and its conjugates). Naringin and total naringenin were rapidly and widely distributed to all the tissues except brain in rats. They had difficulties in crossing the blood-brain barrier. There are no accumulations in rats. This study identifying naringin in several organs including lung and trachea may explain its effects as antitussive.
Keywords: antitussive; naringin; naringenin; tissue distribution; LC-MS/MS; rats